If (3--tan^2A)/(1--3tan^2A) = k. then find cosecA(3sinA-- 4sin^3A) in terms of k

We have,     3 - tan2A1 - 3 tan2A = k3 tan A - tan3Atan A1 - 3 tan2A = k3 tan A - tan3A1 - 3 tan2Atan A = ktan 3Atan A = k    ....1Now, tan 3Atan A - 1 = k - 1tan 3A - tan Atan A = k- 1sin 3Acos 3A - sin Acos Asin Acos A = k - 1sin 3A . cos A - cos 3A . sin Acos A . cos 3A × cos Asin A = k - 1sin3A - Asin A . cos 3A = k - 1sin 2Asin A . cos 3A = k - 12 sin A . cos Asin A . cos 3A = k - 12 cos Acos 3A = k - 1    .....2Dividing 2 by 1, we get      2 cos Acos 3A ×tan Atan 3A = k - 1k2 cos Acos 3A × sin Acos A × cos 3Asin 3A = k - 1ksin Asin 3A = k - 12ksin 3Asin A = 2kk - 1cosec A 3 sin A - 4 sin3A = 2kk - 1

  • -3
What are you looking for?